RUSSIA’S STRATEGIC INTERESTS IN CENTRAL ASIA TODAY - LAUMULIN, Murat (CENTRAL ASIA AND THE CAUCASUS, 2009)
Russia’s policy in Central Asia has arrived at a new stage in its development. This is confirmed both by the transformation of the situation in the region and by the changes in Russia’s international position. At the previous stage in its Central Asian policy, Moscow was busy trying to implement the so-called Putin Doctrine. This basically consisted of attempts to integrate the post-Soviet expanse (encompassing as much territory as possible) by primarily economic means. However, political means were also implied along with the economic levers. This policy was manifested in the various integration formations that sprang up in the CIS, such as the EurAsEC-Customs Union, the SES, the CSTO, and the Belarus-Russia Union State, as well as the multitude of bilateral and multilateral agreements with Russia’s participation in economic trade cooperation, the energy industry, and transportation and communications. This approach was most intensively implemented between 2003 and 2006, when Moscow was able to greatly fortify its position in Central Asia, enter long-term contracts in the production and transportation of energy resources, take partial or complete control over the strategic branches of several regional countries, and achieve advantageous conditions for building pipelines. In addition, the economic penetration of Russian companies into the region was accompanied by intensification of military-technical and military-strategic cooperation between the Russian Federation and the regional states, the setting up of Russian military bases, and the ousting of rivals (with the exception of China). However, after 2006 Russia’s international position began to change, which could not help but have an effect on its Central Asian policy. Another spiral of the confrontation with the West began, pulling Moscow along with it and turning the region into an area where their interests clash